DRUG ABSORPTION ENHANCING PROPERTIES OF ALOE VERA ACROSS INTESTINAL EPITHELIUM - Chen, W.; Hamman, J.; Vlijoen, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Oral drug delivery is considered as the preferred route of administration, but the bioavailability of orally administered hydrophilic, macromolecular drugs is usually poor because of the hostile gastric environment and also poor gastrointestinal mucosal permeability. Co-administration of absorption enhancers is one way to improve oral bioavailability of these drugs. Numerous classes of compounds have been reported to enhance the intestinal absorption of poorly absorbable drugs, but most of them have toxic effects and are not highly efficient. Therefore, development of safe and effective absorption enhancers is still a challenge.The effect of Aloe vera (L.) Burm.f. (Aloe barbadensis Miller) gel and whole leaf extract on the permeability of Caco-2 cell monolayers was determined. Both the A. vera gel and whole leaf extract were able to significantly reduce the transepithelial electrical resistance of the Caco-2 cell monolayers at concentrations above 0.5 % w/v and thereby showed the ability to open tight junctions between adjacent cells. This effect was fully reversible as the electrical resistance of the cell monolayers returned to the original value upon removal of the test solutions. The A. vera gel and whole leaf extract solutions significantly enhanced the transport of insulin across the Caco-2 cell monolayers compared to the control. The results suggest that these plant products have a high potential to be used as absorption enhancers in novel dosage forms for drugs with poor bioavailabilities when administered orally.